Duroplasty for injured cervical spinal cord with uncontrolled swelling: protocol of the DISCUS randomized controlled trial - Saadoun, S; Grassner, L; Belci, M; Cook, J; Knight, R; Davies, L; Asif, H; Visagan, R; Gallagher, MJ; Thomé, C; Hutchinson, PJ; Zoumprouli, A; et al. (BioMed Central, 2023)
Background Cervical traumatic spinal cord injury is a devastating condition. Current management (bony decompression) may be inadequate as after acute severe TSCI, the swollen spinal cord may become compressed against the surrounding tough membrane, the dura. DISCUS will test the hypothesis that, after acute, severe traumatic cervical spinal cord injury, the addition of dural decompression to bony decompression improves muscle strength in the limbs at 6 months, compared with bony decompression alone.